ASSESSMENT OF PHOSPHORUS AVAILABILITY FROM UNREACTIVE TOGO PHOSPHATE ROCK BY LEGUME AND CEREAL CROPS IN TWO GHANAIAN SOILS - Boateng, Alex; Bennoah, Prof. Emmanuel Owusu- (International Journal of Agriculture, 2020)
Purpose: In recent years, phosphate rock (PR) for direct application has been tested in tropical acid soils as a potential alternative to conventional water-soluble P fertilizers like Single Superphosphate (SSP) and Triple Superphosphate (TSP). However, direct application of PR with low reactivity does not always give satisfactory results. Legume and cereal crops represent a strategy that can be used to solubilize P from some of these unreactive PRs. The objective of this study was to assess the availability of P from unreactive Togo Phosphate Rock (TPR) relative to TSP by six (6) crop species in two Ghanaian soils. Methodology: The study was conducted in the greenhouse of the Crop Science Department, University of Ghana. Three P rates, 0mg, 50mg and 100mg P of TPR and TSP were applied to a kilogram of soil per pot in the two soil series. Randomized Complete Block Design was used to do the analyses. Results/Findings: Application of TSP resulted in higher dry matter and P uptake irrespective of the soil type. Among the legumes, cowpea gave the highest dry matter yield. Fairly, a similar trend was obtained with the application of TPR. Among the cereals, the average P uptake by sorghum from TPR was the highest, followed by maize and millet in the Nzema soil. In the Adenta series, P uptake by maize was the highest, followed by sorghum and millet. Phosphorus (P) uptake by the cereals from TPR was generally better in the Adenta than the Nzema soil. Unique contribution to theories, practice and policy: Results show increasing the rate of TPR to 100mg P/pot resulted in an increase in dry matter yield and P uptake in both soils, but was inferior to 100mg P/pot TSP application. Consequently, the rate of application of TPR should always be high if farmers want the best from their investments. Again, the low relative agronomic effectiveness of TPR for all the crops, proved the low reactivity of the material and its subsequent low performance compared with the water-soluble P. The low reactivity and the high molar mass of PO43-/CO32- of the TPR will always make it difficult for P to be made available from the TPR despite the acidity of the soil, the high density of the crops and the ability of the tested crops to exude organic acids, which facilitate phosphorus availability from TPR, therefore making TPR unsuitable for direct application.